2020
DOI: 10.1164/rccm.201909-1771oc
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cardiac Magnetic Resonance Imaging Thresholds for Risk Stratification in Pulmonary Arterial Hypertension

Abstract: Rationale: Pulmonary arterial hypertension (PAH) is a life-shortening condition. The European Society of Cardiology and European Respiratory Society and the REVEAL (North American Registry to Evaluate Early and Long-Term PAH Disease Management) risk score calculator (REVEAL 2.0) identify thresholds to predict 1-year mortality. Objectives: This study evaluates whether cardiac magnetic resonance imaging (MRI) thresholds can be identified and used to aid risk stratification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 42 publications
3
100
0
5
Order By: Relevance
“…1(C) ) and reduced LV volume, RV ejection fraction (RVEF), and stroke volume (SV) are noted to be prognostic markers for PAH [ 14 ]. When used in conjunction with existing risk assessment tools, these CMR markers show increased value over current prognostic methods for risk classification [ 15 , 16 ••]. After adjusting for age, sex, and body surface area, 11% could be reclassified as having a higher risk and 36% a lower risk of 1-year mortality [ 16 ••].…”
Section: Mass Volumes and Functionmentioning
confidence: 99%
“…1(C) ) and reduced LV volume, RV ejection fraction (RVEF), and stroke volume (SV) are noted to be prognostic markers for PAH [ 14 ]. When used in conjunction with existing risk assessment tools, these CMR markers show increased value over current prognostic methods for risk classification [ 15 , 16 ••]. After adjusting for age, sex, and body surface area, 11% could be reclassified as having a higher risk and 36% a lower risk of 1-year mortality [ 16 ••].…”
Section: Mass Volumes and Functionmentioning
confidence: 99%
“…An update, REVEAL 2.0, has recently been published [9] which, in an independent cohort, demonstrated 1-year mortality estimates of 2.6%, 8.6% and 25.4% for low-, intermediate-and high-risk groups respectively, with 5-year estimates of 16.1%, 41.5% and 88.0%, respectively [41]. Additionally, a study using CMR of RV end systolic volume index adjusted for age and sex has been shown to further improve risk stratification for 1-year mortality when used with either the REVEAL 2.0 score or a modified French Pulmonary Hypertension Risk score [13].…”
Section: Bnp/nt-probnp and Comparison With Pulmonary Haemodynamics Ementioning
confidence: 99%
“…For assessment of RV function, cardiac magnetic resonance (CMR) imaging is the gold standard [11][12][13], but cost, availability and until recently the paucity of data on its value in risk stratification [13] have limited its use. Active B-type natriuretic peptide (BNP; or brain natriuretic peptide) and the functionally inert N-terminal prohormone of BNP (NT-proBNP) are well-established clinical biomarkers used in PAH and other cardiovascular disorders, such as acute/chronic heart failure and are used as surrogate markers of cardiac function [1,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…RV dysfunction is related to the severity of PAH and clinical status of the patient [19]. Lewis and colleagues recently evaluated and validated right-ventricular CMR parameters for risk stratification in PAH [20]. In this study, patients were divided into low, intermediate, and high risk according one-year mortality, and RV EF was as follows: >54%, 37%-54%, and <37%.…”
Section: Discussionmentioning
confidence: 99%